2015
DOI: 10.3109/00498254.2015.1067935
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of pretomanid in rat brain via mass spectrometry imaging

Abstract: 1. Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) combines the sensitivity and selectivity of mass spectrometry with spatial analysis to provide a new dimension for histological analyses of the distribution of drugs in tissue. Pretomanid is a pro-drug belonging to a class of antibiotics known as nitroimidizoles, which have been proven to be active under hypoxic conditions and to the best of our knowledge there have been no studies investigating the distribution and localisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Matrix assisted laser desorption ionization mass spectrometry imaging (MALDI MSI) is a label‐free technique, which offers the advantage of determining the distribution of parent drug and metabolites simultaneously . We have recently shown that a combination of liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) with MALDI MSI provides better correlation than PET imaging technique . The aim of this study was to establish methods for the preclinical evaluation and localization of fluoroquinolones in the rat brain by using LC‐MS/MS and MALDI MSI as sensitive tools for its determination.…”
Section: Introductionsupporting
confidence: 84%
“…Matrix assisted laser desorption ionization mass spectrometry imaging (MALDI MSI) is a label‐free technique, which offers the advantage of determining the distribution of parent drug and metabolites simultaneously . We have recently shown that a combination of liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) with MALDI MSI provides better correlation than PET imaging technique . The aim of this study was to establish methods for the preclinical evaluation and localization of fluoroquinolones in the rat brain by using LC‐MS/MS and MALDI MSI as sensitive tools for its determination.…”
Section: Introductionsupporting
confidence: 84%
“…1 In the most recent TB drug pipeline, there are several novel agents, many of which are currently undergoing clinical trials to determine their potential against TB. [2][3][4][5][6][7][8] Amongst them, BDQ has proven to be a promising rst-in-class US FDA approved anti-TB agent, which belongs to the diarylquinoline class of antibiotics. BDQ is proposed for the treatment of multidrugresistant tuberculosis (MDR-TB) in combination with other active anti-TB drugs, when an effective therapy regimen could not be established.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research group studied the localization and bio-distribution of TB drugs (clofazimine, linezolid, rifampicin, pretomanid, TBA-354) in the rodent brain. [2][3][4]6,7,22 However, these drugs offer partial protection in the CNS, thus further improvements in TB chemotherapy is required. 3,4 At present, limited data is available on the localization and distribution of BDQ in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggests bedaquiline penetrates the BBB poorly 5 . Pretomanid penetrates well in animal studies (no human studies exist) 6 .Linezolid is known to have excellent penetration 7 .…”
Section: Discussionmentioning
confidence: 99%